Formulation and evaluation of clarithromycin microspheres for eradication of Helicobacter pylori - Rajinikanth P.S.; Karunagaran L.N.; Balasubramaniam J.; Mishra B. (My University, 2025)
The objective of the study was to develop a stomach-specific drug delivery system for controlled release of clarithromycin for eradication of Helicobacter pylori (H. pylori). Floating-bioadhesive microspheres of clarithromycin (FBMC) were prepared by emulsification-solvent evaporation method using ethylcellulose as matrix polymer and Carbopol 934P as mucoadhesive polymer. The prepared microspheres were subjected to evaluation for particle size, incorporation efficiency, in vitro buoyancy, in vitro mucoadhesion and in vitro drug release characteristics. The prepared microspheres showed a strong mucoadhesive property with good buoyancy. The formulation variables like polymer concentration and drug concentration influenced the in vitro drug release significantly in simulated gastric fluid (pH. 2.0). The in vivo H. pylori clearance efficiency of prepared FBMC in reference to clarithromycin suspension following repeated oral administration to H. pylori infected Mongolian gerbils was examined by polymerase chain reaction (PCR) technique and by a microbial culture method. The FBMC showed a significant anti-H. pylori effect in the in vivo gerbil model. It was also noted that the required amount of clarithromycin for eradication of H. pylori was significantly less in FBMC than from corresponding clarithromycin suspension. The results further substantiated that FBMC improved the gastric stability of clarithromycin (due to entrapment within the microsphere) and eradicated H. pylori from the gastrointestinal tract more effectively than clarithromycin suspension because of the prolonged gastrointestinal residence time of the formulation. © 2008 Pharmaceutical Society of Japan.